Implementasi Smart Home dengan Virtual Assistant pada Perangkat Rumah Tangga - Hidayatulloh, A. Muzzaki Hidayatulloh; Dirgantoro, Guruh Putro; Rokhim, Auliyaur (Multidisciplinary Applications of Quantum Information Science (Al-Mantiq), 2025)
The increasing demand for automated systems that can assist homeowners in managing their electronic devices without physical effort forms the backdrop of this research. With the advancement of Internet of Things (IoT) technology, the concept of a smart home has become more relevant, aiming to provide various conveniences to users. The integration of virtual assistants in smart home systems is seen as a key innovation to enhance the overall user experience. This research focuses on the design and implementation of a smart home system that utilizes a virtual assistant to control household to enhance efficiency and convenience in managing household electronic equipment through voice commands. The system uses a Raspberry Pi as a microcontroller connected devices to control lights and doors. The research involves system design, hardware development, and software development. The test results show that the system can execute user commands with high accuracy, such as turning lights on and off and automatically locking and unlocking doors. This research indicates that implementing a smart home with a virtual assistant for household devices can improve efficiency and convenience in managing household appliances. The system also shows potential for further development by adding additional features such as integration with security alarms and the ability to record user habits to create a more personalized and intuitive experience.